(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
One of the most important problems in degraded mined ecosystem is contamination of soil and water by toxic substances, mainly heavy metal such as Pb and others such as cyanide. Phytoremediation could be used as an alternative technique to overcome this problem. Phytoremediation is defined as clean up of pollutans primarily mediated by photosynthetic plants. These plants have several beneficial characteristics such as the ability to accumulate metal in their shoots and an especially high tolerance to heavy metals. This research was carried out to study the potencies of local species to accumulate Pb and cyanide. Seventeen species were collected from mined waste area (namely tailing area) and then the cyanide and Pb accumulated in each species were analyzed. The result showed that some species accumulated Pb and cyanide in high concentration such as Ipomoea sp. (35.70 ppm cyanida) and Mikania cordata (Burm.f.) B.L.Robinson (11.65 ppm Pb). A series of research is needed to prove that these species are potential as heavy metal and cyanide accumulators. Â© 2005 Jurusan Biologi FMIPA UNS Surakarta Keywords: phytoremediation, heavy metal, gold mined